Upaya Meningkatkan Keterampilan Menulis Siswa Melalui Metode EJA di Kelas Rendah - Nadila Sabrin; Neneng Ernawati (BADAN PENERBIT STIEPARI PRESS, 2024)
Writing ability is one of the productive language skills, meaning that with the ability to read and write students can produce work in written form. Many things are involved when someone writes. Think regularly and logically, be able to express ideas clearly, and be able to use language effectively and apply rules in writing. Improving students' writing skills through the spelling method in lower grades has proven to be effective in various aspects. First, the spelling method helps build a basic understanding of letters and syllables, which are basic skills in writing. By understanding how to spell words correctly, students can build a strong foundation for their writing skills. Second, the spelling method stimulates student creativity. By inviting students to create sentences or stories by spelling, they can express their ideas and imagination more freely. This process not only involves the technical aspects of writing, but also develops creative and narrative thinking skills. In developing students' writing skills in lower grades, this method paves the way for holistic learning, bringing together technical, creative and functional aspects of writing. By proving its effectiveness, the spelling method makes a positive contribution to students' literacy development at the elementary level